Лингвостилистические изменения в русской газете последнего десятилетия - КОЖИНА, МАРГАРИТА Н.; ДУСКАЕВА, Л. П. (Stylistyka, 2021)
Quite noticeaЫe linguo-stylistic changes in Russian newspapers of 1980-1993 (Ьrought to 1ife Ьу perestroik.a and social changes in the 1ife of society) are investigated in the ligЬt of the basic functions, stylistic features and the major principles in the selection and use of the language means in newspapers. The autlюrs draw the conclusion that а11 the basic stylistic parametres of the newspaper are preserved being somelюw modified. Тhе changes mainly relate to tЬе semantic - stylistic level (in addition to the lexical level) and а wide use of collouialisms. Тhе latter is explained Ьу the change in the status of the addresser and the addressee, i.e. the dialogic relations between them. Тhе proЬlem is considered in tЬе second part of the article written wiμt а wide use of examples from newspapers.